Gastronomic Revolution: Peruvian Cuisine’s Journey from Cultural Entity to Commodity - Bannister, Hannah (Undergraduate Research Journal for the Humanities, 2017)
The commodification of culture occurs when cultural products gain additional value beyond standard use-value, moving from a non-commercial realm to the commercial. Before ascending to the global culinary stage, Peruvian cuisine underwent a series of changes as the government, a group of Peruvian elites, and chefs explored ways to increase the cuisine’s market potential, in an era deemed the gastronomic revolution. This research examines the evolution of cuisine through a qualitative analysis of media portrayals and scholarly understandings of the gastronomic revolution and Peruvian cuisine. I argue that the gastronomic revolution in Peru is contributing to the commodification of Peruvian food culture. Though Peru stands to benefit economically from the transformation of Peruvian cuisine, the contributions of minority groups to cuisine could be left behind in selling Peruvian food culture to a global audience.